Biocatalytic synthesis of quinoline derivatives via α-amylase catalysed one-pot domino aza-Michael/Aldol/aromatization reactions. (21st December 2021) - Dutt, Sunil; Tyagi, Vikas
Graphical abstract: Highlights: Biocatalytic synthesis of quinoline derivatives. α-Amylase catalysed one-pot domino aza-Michael/Aldol/aromatization cascade. Highly green and efficient synthesis. Successful scalability up-to gram level. Abstract: Quinoline moiety is a part of various drug molecules and natural products. Previously, a number of catalysts have been made available to synthesize substituted quinolines. Herein, we are reporting α-amylase catalysed synthesis of substituted quinolines via one-pot domino aza-Michael/Aldol/aromatization reactions. Moreover, the α-amylase enzyme from Aspergillus oryzae was found to catalyse the cascade reaction of various 2-aminobenzaldehydes with α, β-unsaturated carbonyls in high catalytic efficiency (56–86% yield).